Pharmaceutical marketing ethics in healthcare quality for patient satisfaction: an Islamic approach - Haque, A. K. M. Ahasanul; Kabir, Sardar Md Humayun; Tarofder, Arun Kumar; Anwar, Naila; Yasmin, Farzana; Maziz, Nazmul Hasan (Advanced Scientific Research, 2019)
ABSTRACT Patients are the center of healthcare system where key role players include pharmaceutical manufacturers. In recent years, ethical standards of marketing strategies conducted by pharmaceutical manufacturers have declined significantly which raises the question of healthcare quality. The conventional way of pharmaceutical marketing is widely accepted by Muslims and non-Muslims around the world. Limited studies have been conducted so far to establish Islamic marketing mechanism in pharmaceutical business as Islam is the answer to all questions of our lives and beyond. This paper theoretically proposed the relation of pharmaceutical marketing strategies with quality healthcare service for patient’s satisfaction and investigated it with primary data. It also highlights the mediating effect of Islamic marketing mechanism from ethical context. The findings revealed that there is a significant positive relationship exists between pharmaceutical marketing ethics and Islamic marketing mechanism which partially mediates healthcare quality. Also, healthcare quality significantly influences patient satisfaction. The framework developed in this study need to be tested in the future through other social factors. Based on the findings, recommendations for Muslim entrepreneurs are explained at the end.